ROLE OF ARTIFICIAL NEURAL NETWORK IN OPINION CLASSIFICATION - Josephine V L, Helen; Thiyagarajan, Gomathi; Anita Sofia, V. S. (International Journal of Psychosocial Rehabilitation, 2020)
In the present world, internet users are expanding rapidly, and consumers are more involved in searching for and selecting the best product. E-commerce organizations also spend a lot of time, effort, and cost to investigate the comments and feedback about their products. This scrutiny would assist the corporations to enhance their services and products at low cost, which in turn would facilitate them to extend and flourish in the industry. Extracting knowledge from vast unstructured data, which is in the form of customer reviews, finds it very difficult to analyze and evaluate. This research paper analyzes the role of neural networks in opinion mining classification and proposes a gain ratio feedforward neural network (GR_FFNN) algorithm to improve classification accuracy. This paper also compares the GR_FFNN algorithm with the existing neural network classifier.